Nanometer silicon inlaid silicon monoxide / carbon composite negative electrode material and preparation method thereof

By using nano-silicon embedded silicon oxide/carbon composite anode material in lithium-ion batteries, the large-volume expansion problem of silicon anode material during lithium-integrated/deliquefaction is solved, and high specific capacity and excellent electrochemical performance are achieved, which is suitable for large-scale production.

CN119601602AActive Publication Date: 2025-03-11ANHUI UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411681602.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-11
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the large volume expansion of the silicon negative electrode material during the lithium-embedding/deliquefaction process leads to the material's rupture and powderization, resulting in capacity attenuation and poor electronic conductivity. In addition, traditional preparation methods have problems such as nano-Si oxidation, low specific capacity and thermal treatment temperature limitation.

Method used

The preparation method of nano-silicon-laminated silicon oxide/carbon composite anode material is adopted. The carbon-coated nano-SiO2 is reduced to nano-Si-laminated SiOx by low-temperature molten salt aluminum thermal reduction, and an asphalt polymerization accelerator is introduced under conditions below 900°C to improve the structural order of asphalt pyrolyzed carbon.

Benefits of technology

It effectively avoids the oxidation of nano Si, improves the specific capacity, enhances the reversibility and rate performance of electrochemical reactions, and is simple in process and low in cost, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601602A_ABST
    Figure CN119601602A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion battery negative electrode materials, and particularly relates to a nanometer silicon inlaid silicon monoxide / carbon composite negative electrode material and a preparation method thereof. The preparation method comprises the following steps: by taking hydrophobic nano silicon dioxide and asphalt as main raw materials, dissolving the asphalt in carbon tetrachloride, mixing the nano silicon dioxide with an asphalt solution, and carrying out heat treatment to prepare carbon-coated silicon dioxide powder; mixing the carbon-coated silicon dioxide powder with aluminum powder, potassium chloride and anhydrous aluminum chloride, and reducing to obtain carbon-coated nano silicon inlaid silicon monoxide powder; mixing the carbon-coated nano-silicon inlaid silicon monoxide with the asphalt carbonization product, and carrying out ball milling; and mixing the ball-milled product with asphalt, styrene and imidazoline, carrying out ball milling in a carbon tetrachloride medium, and carrying out heat treatment on the ball-milled product to prepare the nano silicon inlaid silicon monoxide / carbon composite negative electrode material. The method disclosed by the invention is simple in process, relatively low in cost, environment-friendly and easy to realize large-scale production, and the prepared negative electrode material has excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of negative electrode materials for lithium ion batteries, and in particular relates to a nano-silicon embedded silicon oxide / carbon composite negative electrode material and a preparation method thereof. Background Art

[0002] Silicon (Si) is a representative negative electrode material for the next generation of lithium-ion batteries due to its advantages such as high theoretical capacity, suitable working potential and high natural abundance. However, due to the inherent large volume expansion (up to 300%) during the lithium insertion / extraction process, the active Si particles break and pulverize, causing the solid electrolyte interface film (SEI) to be unstable, and ultimately leading to severe capacity decay of Si negative electrode materials. In addition, pure Si materials have poor electronic conductivity and are difficult to support high-rate charge and discharge. In order to solve these problems, combining nano-sized Si with different carbon materials to form Si / C composite negative electrode materials with different structures has been proven to be a promising method that can largely overcome the inherent shortcomings of silicon negative electrode materials.

[0003] As a byproduct of the petroleum industry, asphalt has the advantages of high aromaticity, high carbon-hydrogen ratio, low price and wide sources. It is a high-quality carbon precursor for silicon-carbon negative electrode materials of lithium-ion batteries. Coating asphalt on the surface of Si forms a carbon coating on the surface of Si after heat treatment, which can buffer volume expansion and form a stable SEI film, thereby improving the cycle performance of the electrode material; in addition, carbon-coated Si has good conductivity, which can improve the rate performance of the electrode material.

[0004] At present, the common preparation method of commercial Si / C composite negative electrode materials is to uniformly disperse nano-Si and graphite in molten asphalt, or to uniformly disperse nano-Si and graphite in asphalt / CCl4 or asphalt / tetrahydrofuran (C4H8O) solutions to obtain asphalt / graphite / Si precursors, and then obtain Si / C composite negative electrode materials through high-temperature inert atmosphere heat treatment.

[0005] The above method for preparing Si / C composite negative electrode materials has obvious disadvantages: first, the nano-Si reaction activity is extremely high, and it is easy to react with oxygen-containing functional groups and water vapor in asphalt during the heat treatment process, resulting in partial oxidation of nano-Si, causing problems such as reduced coulombic efficiency and capacity of the final Si / C negative electrode material; second, in order to reduce the effect of active Si expansion on the cycle stability of Si / C composite negative electrode materials, the content of nano-Si in the composite material prepared by this method is relatively low (usually 20wt%), resulting in a low maximum specific capacity of the prepared Si / C composite negative electrode material (usually 800mAh g -1); Third, in order to prevent Si from reacting with C to form SiC, the heat treatment temperature of the asphalt / Si precursor cannot exceed 900°C, which results in a low structural order of the asphalt pyrolysis carbon, and ultimately causes the electrochemical reaction reversibility and rate performance of the Si / C composite negative electrode material to be poor. Summary of the invention

[0006] The purpose of the present invention is to overcome the above problems existing in the conventional technology and provide a nano-silicon embedded silicon oxide / carbon composite negative electrode material and a preparation method thereof. The present invention can effectively reduce the carbon-coated nano-SiO2 to obtain a carbon-coated nano-Si embedded SiO2 x The thin flaky asphalt pyrolysis carbon introduced can effectively relieve the stress caused by the volume expansion of Si. The addition of asphalt polymerization accelerator makes the asphalt coated on the surface of the active material still have a high degree of structural order at a temperature below 900 °C. x The preparation method of the carbon / carbon composite negative electrode material is not only simple in process, high in efficiency, low in cost, environmentally friendly, and easy to achieve large-scale production, but also the prepared lithium-ion battery negative electrode material has excellent comprehensive electrochemical properties.

[0007] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:

[0008] The present invention provides a method for preparing a nano-silicon-embedded silicon oxide / carbon composite negative electrode material, comprising the following steps:

[0009] 1) According to a certain weight ratio, appropriate amounts of nano-SiO2 and asphalt are dispersed in CCl4, and after ultrasonic treatment, stirred at 30-70°C for 5-8h, the obtained product is vacuum dried, and then heat treated for a period of time at a certain temperature in an inert atmosphere to obtain carbon-coated nano-SiO2 powder;

[0010] 2) uniformly mixing the carbon-coated nano-SiO2 powder obtained in step 1) with Al powder according to a certain molar ratio to obtain a redox reaction system; uniformly mixing anhydrous AlCl3 with KCl according to a certain molar ratio to obtain an AlCl3-KCl binary mixed salt system; uniformly mixing the reaction system and the mixed salt system according to a certain weight ratio, and heating them at a certain temperature and in an inert atmosphere for a period of time to obtain a carbon-coated nano-Si embedded SiO2 system. x ;

[0011] 3) In a certain weight ratio, the carbon-coated nano-Si prepared in step 2) is embedded in SiO x Evenly mix with pitch carbon prepared under certain conditions, add appropriate amount of CCl4, fill with inert gas, and perform ball milling under certain conditions;

[0012] 4) Mixing the ball milling product obtained in step 3), asphalt, styrene monomer and imidazoline in a certain weight ratio, and evenly mixing them in a CCl4 medium, reacting the ball milling product in an inert atmosphere at a certain temperature for a period of time, and then heat treating at a certain temperature for a period of time to obtain a nano-Si embedded SiO x / carbon composite negative electrode material.

[0013] Furthermore, in step 1), the particle size of the nano-SiO2 is 10 to 50 nm.

[0014] Furthermore, in step 1), the asphalt is an asphalt having a residual carbon content of 15-25% after heat treatment at 1100° C. in an inert atmosphere.

[0015] Furthermore, in step 1), the weight ratio of nano-SiO2 to asphalt is 1:0.25-0.30, the heat treatment temperature is 900-1100°C, and the heat treatment time is 2-4h.

[0016] Furthermore, in step 2), the molar ratio of nano-SiO2 powder to Al powder in the reaction system is 1:1.5-2.5, the molar ratio of anhydrous AlCl3 to KCl in the mixed salt system is 1:0.7-0.8, the weight ratio of the reaction system to the mixed salt system is 1:4.0-5.0, the heating temperature is 350-450°C, and the heating time is 10-12h.

[0017] Furthermore, in step 3), the asphalt carbon is a product of heat treatment of asphalt in an Ar gas atmosphere, the heat treatment temperature is 1000-1200°C, and the heat treatment time is 2-4 hours; the weight ratio of carbon-coated silicon oxide / silicon to asphalt carbon is 1:0.15-0.25, the ball milling speed is 350-450rpm, the ball milling time is 6-10 hours, and the weight ratio of material in the ball mill to grinding balls is 1:60-100.

[0018] Furthermore, in step 4), the weight ratio of the ball milling product to asphalt is 1:0.50-0.60, the weight ratio of asphalt to styrene and imidazoline is 1:0.7:0.002; the ball mill speed is 250-350 rpm, the ball milling time is 2-4 h, the weight ratio of the material in the ball mill jar to the grinding balls is 1:60-100; the reaction temperature is 140-180°C, the reaction time is 6-10 h, the heat treatment temperature is 850-950°C, and the heat treatment time is 2-4 h.

[0019] The present invention also provides a nano-silicon embedded silicon oxide / carbon composite negative electrode material, which is prepared by the above-mentioned preparation method.

[0020] The beneficial effects of the present invention are:

[0021] 1. The present invention can efficiently reduce carbon-coated nano-SiO2 to carbon-coated nano-Si@SiO by low-temperature molten salt aluminothermic reduction. x , and nano-Si is embedded in SiO x This avoids the problem of oxidation of highly active nano-Si by oxygen-containing functional groups in asphalt and water vapor during the current heat treatment process for the preparation of Si / C composites.

[0022] 2. Carbon-coated nano-Si embedded SiO obtained by reduction x , among which amorphous SiO x It provides a relatively considerable specific capacity. At the same time, its volume change during the charge and discharge process is much smaller than that of Si. The volume change of the electrode material during the charge and discharge process is significantly reduced. Therefore, the electrode active material Si / SiO x The content can be as high as 67wt% or more, overcoming the problems of low weight proportion of active components and small specific capacity in current Si / C negative electrode materials.

[0023] 3. The present invention physically and uniformly mixes asphalt, styrene and imidazoline by ball milling, thereby promoting asphalt polymerization, overcoming the low degree of carbon order and low content of microcrystalline carbon in the current Si / C composite negative electrode material after low-temperature (900°C) pyrolysis of asphalt, and effectively improving the reversibility and rate performance of the electrochemical reaction of the composite material.

[0024] 4. The nano-Si@SiO prepared by the present invention x The / C composite negative electrode material exhibits excellent electrochemical performance, and the preparation method is simple, the equipment is simple, the cost is low, the environment is friendly, and it is easy to achieve mass production. The prepared electrode material has a conductivity of 0.05A g -1 The first cycle discharge / charge capacity is 2552.8 / 1609.4mAh g -1 , the first coulombic efficiency is 63.0%; when the current is increased to 2.0A g -1 The measured reversible capacity is 948.6 mAh g -1 , the capacity retention rate is as high as 54.9%; at 0.50A g -1 After 200 cycles, the capacity of the electrode material is still as high as 714.4 mAh g -1 , the capacity retention rate is 82.6%.

[0025] Of course, any product implementing the present invention does not necessarily need to achieve all of the above advantages at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0027] Figure 1 The nano-Si@SiO prepared in Example 1 x / XRD pattern of C negative electrode material;

[0028] Figure 2 The nano-Si@SiO prepared in Example 1 x XPS graph of / C negative electrode material;

[0029] Figure 3 The nano-Si@SiO prepared in Example 1 x FESEM image of / C negative electrode material;

[0030] Figure 4 The nano-Si@SiO prepared in Example 1 x TEM image of / C negative electrode material;

[0031] Figure 5 This is a test diagram of a battery sample assembled with the nano-Si@SiOx / C negative electrode material prepared in Example 1;

[0032] Where: (a) is 0.05A g -1 Constant current charge and discharge curves under current density, (b) rate curves under different current densities; (c) at 0.5A g -1 Cycling performance curves under different current densities. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] The present invention adopts nano-SiO2 and asphalt as main raw materials, disperses the nano-SiO2 and asphalt in CCl4, heats and stirs, and then dries and heats in an inert atmosphere to obtain carbon-coated nano-SiO2; uniformly mixes the carbon-coated nano-SiO2, Al powder, KCl and anhydrous AlCl3, and heats in an inert atmosphere to obtain carbon-coated nano-Si embedded SiO x ; Inlay carbon-coated nano-Si into SiOx The ball milling product is mixed with asphalt pyrolysis carbon, and the ball milling product is evenly mixed with asphalt, styrene and imidazoline in CCl4 medium, and then heat-treated in an inert atmosphere to finally obtain a nano-silicon embedded silicon oxide / carbon composite negative electrode material.

[0035] The invention can effectively avoid the problem of oxidation of active nano-Si and low specific capacity of Si / C composite material during heat treatment. This is because firstly, during the stirring process of nano-SiO2 in asphalt / CCl4 solution at a certain temperature, asphalt is uniformly coated on the surface of nano-SiO2 as CCl4 evaporates, and after being treated in an inert atmosphere, a uniform porous carbon coating layer is formed on the surface of nano-SiO2. Then, with the aid of low-temperature molten salt aluminum thermal reduction, a large number of reduced Si atoms are aggregated to form nano-Si, and at the same time, unreduced SiO2 undergoes disproportionation reaction with nano-Si to form SiO x Wrapped on the surface of nano-Si (nano-Si@SiO x ), and the asphalt pyrolysis carbon is coated on nano-Si@SiO x The surface effectively blocks water vapor and highly active nano-Si@SiO x The carbon-coated nano-Si embedded in SiO x , which is mainly composed of SiO x The volume changes little during the charge and discharge process, and provides a relatively considerable specific capacity, which avoids the problem that the content of nano-Si in the current composite material is low, resulting in a low specific capacity of Si / C composite negative electrode materials. The present invention introduces a polymerization promoter into the asphalt, so that the asphalt coated on the surface of the active material still has a high degree of structural order at a thermal decomposition product below 900°C. This is because during the heat treatment process at 140°C, imidazoline can promote the thermal polycondensation reaction of styrene monomer and aromatic compounds in asphalt, so that the planar molecular layer continues to grow, and at the same time, a large number of planar molecular layers are continuously stacked and rearranged, so that the carbonized product has a high degree of structural order and a high content of microcrystals, and is coated on the active component nano-Si@SiO x The surface was finally prepared with nano-Si@SiO x / C) composite negative electrode material.

[0036] The specific embodiments of the present invention are as follows:

[0037] Example 1

[0038] 1) According to the weight ratio of nano-SiO2 to asphalt being 1:0.28, 3.0005 g of nano-SiO2 and 0.8401 g of asphalt were weighed and dispersed in CCl4, and the mixed suspension was placed on a magnetic stirrer and stirred at 50°C for 6 h; the stirred product was vacuum dried and heat treated at 1000°C for 3 h in an Ar gas atmosphere to obtain carbon-coated nano-SiO2;

[0039] 2) According to the molar ratio of nano-SiO2 to Al powder of 1:2.0, 1.0032g of carbon-coated nano-SiO2 and 0.6413g of Al powder were weighed and mixed uniformly, and then according to the weight ratio of the reaction system to the mixed salt system of 1:4.4298 and the molar ratio of anhydrous AlCl3 to KCl of 1:0.75, 5.6367g of anhydrous AlCl3 and 2.3592g of KCl were weighed and mixed uniformly, and the mixed powder was evenly mixed and placed in a corundum crucible, and heat-treated at 400°C for 10h in an Ar gas atmosphere, and then washed and dried with a 9wt% dilute hydrochloric acid solution to obtain a carbon-coated nano-Si embedded SiO x ;

[0040] 3) The asphalt was heat treated at 1100 °C for 3 h in an Ar atmosphere to obtain asphalt pyrolysis carbon, and the carbon-coated nano-Si was embedded in SiO x The weight ratio of carbon to asphalt pyrolysis carbon was 1:0.2009. 0.5056 g of carbon-coated silicon oxide / silicon and 0.1016 g of asphalt carbonization product were weighed, 3 g of CCl4 was added and mixed evenly, and then placed in a polyethylene ball mill and milled at 400 rpm for 8 h using zirconium oxide grinding balls;

[0041] 4) According to the weight ratio of the ball-milled product obtained in step 3) to asphalt of 1:0.5355, the weight ratio of asphalt to styrene and imidazoline of 1:0.7:0.002, 0.5007g of the ball-milled product, 0.2681g of asphalt, 0.1877g of styrene, and 0.0005g of imidazoline were weighed, 3g of CCl4 was added and mixed evenly, and the mixture was placed in a polyethylene ball mill with a zirconia grinding ball at 300rpm for 3h; then, the mixture was incubated at 2°C min in an Ar gas atmosphere. -1 Heat to 140℃, keep at 140℃ for 8h, then -1 The temperature was raised to 900℃ and heat treated for 3h to obtain a nano-silicon embedded silicon oxide / carbon composite negative electrode material (abbreviated as nano-Si@SiO x / C).

[0042] The negative electrode materials prepared in the above steps were assembled into a half-cell and tested at 0.05A g -1 The first cycle discharge / charge capacity is 2552.8 / 1609.4mAh g -1, the first coulombic efficiency is 63.0%; when the current is increased to 2.0A g -1 The measured reversible capacity is 948.6 mAh g -1 , the capacity retention rate is as high as 54.9%; at 0.50A g -1 After 200 cycles, the capacity of the electrode material is still as high as 714.4 mAh g -1 , the capacity retention rate is 82.6%.

[0043] Example 2

[0044] 1) According to the weight ratio of nano-SiO2 to asphalt being 1:0.25, 3.0005 g of nano-SiO2 and 0.7513 g of asphalt were weighed and dispersed in CCl4, and the mixed suspension was placed on a magnetic stirrer and stirred at 50°C for 6 h; the stirred product was vacuum dried and heat treated at 1000°C in an Ar gas atmosphere for 3 h to obtain carbon-coated nano-SiO2;

[0045] 2) According to the molar ratio of nano-SiO2 to Al powder of 1:2.0, 1.0032g of carbon-coated nano-SiO2 and 0.6449g of Al powder were weighed and mixed uniformly, and then according to the weight ratio of the reaction system to the mixed salt system of 1:5.0 and the molar ratio of anhydrous AlCl3 to KCl of 1:0.75, 5.6685g of anhydrous AlCl3 and 2.3725g of KCl were weighed and mixed uniformly, and the mixed powder was evenly mixed and placed in a corundum crucible, and heat-treated at 400°C for 10h in an Ar gas atmosphere, and then washed and dried with a 9wt% dilute hydrochloric acid solution to obtain a carbon-coated nano-Si embedded SiO x ;

[0046] 3) The asphalt was heat treated at 1100 °C for 3 h in an Ar atmosphere to obtain asphalt pyrolysis carbon, and the carbon-coated nano-Si was embedded in SiO x The weight ratio of carbon to asphalt pyrolysis carbon is 1:0.25. Weigh 0.5056g carbon-coated silicon oxide / silicon and 0.1264g asphalt carbonization product, add 3g CCl4 and mix evenly. Place in a polyethylene ball mill and use zirconium oxide grinding balls at 400rpm for 8h;

[0047] 4) According to the weight ratio of the ball-milled product obtained in step 3) to asphalt of 1:0.50, and the weight ratio of asphalt to styrene and imidazoline of 1:0.7:0.002, 0.5007g of the ball-milled product, 0.2504g of asphalt, 0.1752g of styrene, and 0.0005g of imidazoline were weighed, 3g of CCl4 was added and mixed evenly, and the mixture was placed in a polyethylene ball mill with a zirconia grinding ball at 300rpm for 3h; then, the mixture was incubated at 2°C min in an Ar atmosphere. -1 Heat to 140℃, keep at 140℃ for 8h, then-1 The temperature was raised to 900℃ for heat treatment for 3h to obtain a nano-silicon embedded silicon oxide / carbon composite negative electrode material (abbreviated as SiO x / Si@C).

[0048] The negative electrode materials prepared in the above steps were assembled into a half-cell and tested at 0.05A g -1 The first cycle discharge / charge capacity is 2507.3 / 1557.0mAh g -1 The first coulombic efficiency is 62.1%; when the current is increased to 2.0A g -1 The measured reversible capacity is 833.0 mAh g -1 , the capacity retention rate is as high as 52.7%; at 0.50A g -1 After 200 cycles, the capacity of the electrode material is still as high as 698.1 mAh g -1 , the capacity retention rate is 80.4%.

[0049] Example 3

[0050] 1) According to the weight ratio of nano-SiO2 to asphalt being 1:0.30, 3.0005 g of nano-SiO2 and 0.9002 g of asphalt were weighed and dispersed in CCl4, and the mixed suspension was placed on a magnetic stirrer and stirred at 50°C for 6 h; the stirred product was vacuum dried and heat-treated at 1000°C for 3 h in an Ar gas atmosphere to obtain carbon-coated nano-SiO2;

[0051] 2) According to the molar ratio of nano-SiO2 to Al powder of 1:2.0, 1.0032g of carbon-coated nano-SiO2 and 0.6338g of Al powder were weighed and mixed uniformly, and then according to the weight ratio of the reaction system to the mixed salt system of 1:4.4298 and the molar ratio of anhydrous AlCl3 to KCl of 1:0.75, 5.6154g of anhydrous AlCl3 and 2.3503g of KCl were weighed and mixed uniformly, and the mixed powders were evenly mixed and placed in a corundum crucible, and heat-treated at 400°C in an Ar gas atmosphere for 10h, and then washed and dried with a 9wt% dilute hydrochloric acid solution to obtain carbon-coated silicon dioxide / silicon;

[0052] 3) The asphalt was heat treated at 1100 °C for 3 h in an Ar atmosphere to obtain asphalt pyrolysis carbon, and the carbon-coated nano-Si was embedded in SiO x The weight ratio of carbon to asphalt pyrolysis carbon is 1:0.15. Weigh 0.5056g carbon-coated silicon oxide / silicon and 0.0758g asphalt carbonization product, add 3g CCl4 and mix evenly. Place in a polyethylene ball mill and use zirconium oxide grinding balls at 400rpm for 8h;

[0053] 4) According to the weight ratio of the ball-milled product obtained in step 3) to asphalt of 1:0.60, and the weight ratio of asphalt to styrene and imidazoline of 1:0.7:0.002, 0.5007g of the ball-milled product, 0.3004g of asphalt, 0.2103g of styrene, and 0.0006g of imidazoline were weighed, 3g of CCl4 was added and mixed evenly, and the mixture was placed in a polyethylene ball mill with a zirconia grinding ball at 300rpm for 3h; then, the mixture was incubated at 2°C min in an Ar gas atmosphere. -1 Heat to 140℃, keep at 140℃ for 8h, then -1 The temperature was raised to 900°C and heat treated for 3 hours to obtain a nano-silicon embedded silicon oxide / carbon composite negative electrode material (abbreviated as nano-Si@SiOx / C).

[0054] The negative electrode materials prepared in the above steps were assembled into a half-cell and tested at 0.05A g -1 The first cycle discharge / charge capacity is 2498.7 / 1534.2mAh g -1 The first coulombic efficiency is 61.4%; when the current is increased to 2.0A g -1 The measured reversible capacity is 821.4 mAh g -1 , the capacity retention rate is as high as 52.1%; at 0.50A g -1 After 200 cycles, the capacity of the electrode material is still as high as 691.4 mAh g -1 , the capacity retention rate is 81.2%.

[0055] Comparative Example 1

[0056] Step 1) in Example 1 is omitted, the surface of the nano-silicon dioxide is coated in advance, and the nano-silicon dioxide is directly reduced by aluminothermic reduction. The subsequent steps are exactly the same as those in Example 1.

[0057] The negative electrode materials prepared according to the above steps were assembled into a half-cell, and the electrochemical performance was measured as follows:

[0058] At 0.05A g -1 The first cycle discharge / charge capacity is 2120.3 / 1189.5mAh g -1 The first coulombic efficiency is 56.1%; when the current is increased to 2.0A g -1 The measured reversible capacity is 401.2 mAh g -1 , the capacity retention rate is 35.7%; at 0.50A g -1 After 200 cycles, the capacity of the electrode material is 430.2 mAh g -1 , the capacity retention rate is 55.3%.

[0059] Comparative Example 2

[0060] Steps 1) and 2) in Example 1 were implemented, step 3) was omitted, and the subsequent steps were exactly the same as in Example 1.

[0061] The negative electrode materials prepared according to the above steps were assembled into a half-cell, and the electrochemical performance was measured as follows:

[0062] At 0.05A g -1 The first cycle discharge / charge capacity is 2442.3 / 1699.1mAh g -1 , the first coulombic efficiency is 69.5%; when the current is increased to 2.0A g -1 The measured reversible capacity is 7797.9 mAh g -1 , the capacity retention rate is 50.2%; at 0.50A g -1 After 200 cycles, the capacity of the electrode material is 684.2 mAh g -1 , the capacity retention rate is 69.7%.

[0063] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a nano-silicon embedded silicon oxide / carbon composite negative electrode material, characterized in that: The steps include: 1) According to a certain weight ratio, appropriate amounts of nano-SiO2 and asphalt are dispersed in CCl4, and after ultrasonic treatment, stirred at 30-70°C for 5-8h, the obtained product is vacuum dried, and then heat treated for a period of time at a certain temperature in an inert atmosphere to obtain carbon-coated nano-SiO2 powder; 2) uniformly mixing the carbon-coated nano-SiO2 powder obtained in step 1) with Al powder according to a certain molar ratio to obtain a redox reaction system; uniformly mixing anhydrous AlCl3 with KCl according to a certain molar ratio to obtain an AlCl3-KCl binary mixed salt system; uniformly mixing the reaction system and the mixed salt system according to a certain weight ratio, and heating them at a certain temperature and in an inert atmosphere for a period of time to obtain a carbon-coated nano-Si embedded SiO2 system. x ; 3) In a certain weight ratio, the carbon-coated nano-Si prepared in step 2) is embedded in SiO x Evenly mix with pitch carbon prepared under certain conditions, add appropriate amount of CCl4, fill with inert gas, and perform ball milling under certain conditions; 4) Mixing the ball milling product obtained in step 3), asphalt, styrene monomer and imidazoline in a certain weight ratio, and evenly mixing them in a CCl4 medium, reacting the ball milling product in an inert atmosphere at a certain temperature for a period of time, and then heat treating at a certain temperature for a period of time to obtain a nano-Si embedded SiO x / carbon composite negative electrode material.

2. The method for preparing the nano-silicon embedded silicon oxide / carbon composite negative electrode material according to claim 1, characterized in that: In step 1), the particle size of the nano-SiO2 is 10 to 50 nm.

3. The method for preparing the nano-silicon embedded silicon oxide / carbon composite negative electrode material according to claim 1, characterized in that: In step 1), the asphalt is an asphalt having a residual carbon content of 15-25% after heat treatment at 1100° C. in an inert atmosphere.

4. The method for preparing the nano-silicon embedded silicon oxide / carbon composite negative electrode material according to claim 1, characterized in that: In step 1), the weight ratio of nano-SiO2 to asphalt is 1:0.25-0.30, the heat treatment temperature is 900-1100°C, and the heat treatment time is 2-4h.

5. The method for preparing the nano-silicon embedded silicon oxide / carbon composite negative electrode material according to claim 1, characterized in that: In step 2), the molar ratio of nano-SiO2 powder to Al powder in the reaction system is 1:1.5-2.5, the molar ratio of anhydrous AlCl3 to KCl in the mixed salt system is 1:0.7-0.8, the weight ratio of the reaction system to the mixed salt system is 1:4.0-5.0, the heating temperature is 350-450°C, and the heating time is 10-12h.

6. The method for preparing the nano-silicon embedded silicon oxide / carbon composite negative electrode material according to claim 1, characterized in that: In step 3), the asphalt carbon is the product of heat treatment of asphalt in an Ar gas atmosphere, the heat treatment temperature is 1000-1200°C, the heat treatment time is 2-4 hours, the weight ratio of carbon-coated silicon oxide / silicon to asphalt carbon is 1:0.15-0.25, the ball milling speed is 350-450rpm, the ball milling time is 6-10 hours, and the weight ratio of material in the ball mill to grinding balls is 1:60-100.

7. The method for preparing the nano-silicon embedded silicon oxide / carbon composite negative electrode material according to claim 1, characterized in that: In step 4), the weight ratio of the ball milling product to asphalt is 1:0.50-0.60, the weight ratio of asphalt to styrene and imidazoline is 1:0.7:0.002; the ball mill speed is 250-350 rpm, the ball milling time is 2-4 h, the weight ratio of the material in the ball mill jar to the grinding balls is 1:60-100; the reaction temperature is 140-180°C, the reaction time is 6-10 h, the heat treatment temperature is 850-950°C, and the heat treatment time is 2-4 h.

8. A nano-silicon embedded silicon oxide / carbon composite negative electrode material prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Anode active material and manufacturing method therefor

    CN113632262A

  • Nanometer silicon-silicon monoxide negative electrode material with embedded structure and preparation method of nanometer silicon-silicon monoxide negative electrode material

    CN116314714A